2009
DOI: 10.1111/j.1551-2916.2008.02914.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Engineering Properties, Mineralogy, and Microstructure in Cement‐Based Hydroceramic Materials Cured at 200°–350°C

Abstract: Cement‐based materials used to seal geothermal or deep oil wells are exposed to severe conditions. Optimizing engineering properties such as strength and permeability is therefore very important. We have synthesized hydroceramic materials for such applications based on the CaO−Al2O3−SiO2−H2O (CASH) system and cured them over a range of temperatures (200°–350°C). Depending on initial composition and curing temperature, hydroceramics of complex and diverse mineralogy and microstructure are formed. The minerals f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Finally, it is possible that the difference in composition between the two samples affected the mechanical properties. Recent work suggests that increasing xonotlite content at the expense of tobermorite is likely to result in an increase in compressive strength, which would fit with the differences observed here. Previous research, however, has shown that xonotlite was weaker than tobermorite, making it difficult to draw conclusions about the effect of composition on the strengths observed herein.…”
Section: Discussionsupporting
confidence: 84%
“…Finally, it is possible that the difference in composition between the two samples affected the mechanical properties. Recent work suggests that increasing xonotlite content at the expense of tobermorite is likely to result in an increase in compressive strength, which would fit with the differences observed here. Previous research, however, has shown that xonotlite was weaker than tobermorite, making it difficult to draw conclusions about the effect of composition on the strengths observed herein.…”
Section: Discussionsupporting
confidence: 84%
“…Glass components are applied mainly to concrete modification [21][22][23][24][25][26][27][28]. Analyses conducted by the SILICATY Group and others [29][30][31][32] prove that it is possible to limit the amount of lime up to 2% on the condition of good quality sand (rich in Al) or other modifiers are used. Very good results (in particular within the microstructure) are obtained in concrete when an amorphous component (fly ash, glass powder) is added.…”
Section: Introductionmentioning
confidence: 99%
“…Xonotlite, a calcium silicate hydrate, has been industrially produced as a main constituent for heat insulating material [1,2] and building material [3] because of its high stability at high temperature and fibrous crystal form. Xonotlite can be prepared from a silica and calcium hydroxide suspension using a hydrothermal process [4][5][6][7][8][9][10]. The xonotlite crystal formation mechanism from the suspension is complicated and dependent on the reactivity of the raw materials [7][8][9] due to the various intermediate reaction products are formed in the reaction processes.…”
Section: Introductionmentioning
confidence: 99%